2017
DOI: 10.28932/jmh.v1i6.555
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Ethanol Extract Tempuyung Leaf (Sonchus arvensis L.) Against Gentamicin Induced Renal Injury Viewed from Blood Ureum Level

Abstract: Acute renal injury is characterized by decrement of glomerular filtration rate (GFR), resulting in nitrogen metabolic end product retention such as blood ureum. Aminoglycoside nephrotoxic injuries are common in elderly, with mortality rate 50-70%. Tempuyung has been empirically used in relieving renal problems as it contains several active antioxidants. This study aimed to analyze the protective effect of ethanol extract tempuyung leaf (EET) against gentamicin induced renal injury viewed from blood ureum level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
1
3
0
Order By: Relevance
“…Decreased serum urea and creatinine levels revealed an improvement in kidney function of the test animals [30][31][32]. These findings are in line with the report of Imelda et al showed that Sonchus arvensis L. 100 and 200 mg/kg b.w reduced serum urea and creatinine levels after administration of Sonchus arvensis L. extract and gentamicin for ten days, simultaneously [10,33].…”
Section: Discussionsupporting
confidence: 87%
“…Decreased serum urea and creatinine levels revealed an improvement in kidney function of the test animals [30][31][32]. These findings are in line with the report of Imelda et al showed that Sonchus arvensis L. 100 and 200 mg/kg b.w reduced serum urea and creatinine levels after administration of Sonchus arvensis L. extract and gentamicin for ten days, simultaneously [10,33].…”
Section: Discussionsupporting
confidence: 87%
“…The involvement of oxidative stress can cause the amount of antioxidant status to decrease [42]. Oxidative stress condition is defined as imbalance condition between antioxidants and free radicals, where the state of free radicals is higher than antioxidants [14]. The number of antioxidants decreases because the body used to balance the high free radicals due to the presence of parasites.…”
Section: Discussionmentioning
confidence: 99%
“…In Indonesia, Sonchus arvensis L., a highly invasive species of the family Asteraceae, is used as a traditional medicinal plant for malaria treatment [10]. This plant contains various active compounds including flavonoids, saponins, and polyphenols [11], which have been reported for moderate to high antioxidant [12], hepatoprotective [13], nephroprotective [14], anti-inflammatory [15], and antibacterial activities [16][17][18]. Although S. arvensis L. has pharmaceutical benefits, it has never been evaluated for in vivo treatment of malaria.…”
Section: Introductionmentioning
confidence: 99%
“…The diuretic effect obtained comes from ethanol extract of tempuyung leaves with the active antioxidant content of flavonoids. Research shows the effect of protection of ethanol extract tempuyung against kidney injury [14]. In addition, tempuyung leaves can be used as a diuretic drug because they have a high potassium chemical compound content.…”
Section: Diureticsmentioning
confidence: 99%